Trans-frontier capital links between socialist enterprises - Peter Lorenz (Intereconomics, 1978)
It seems reasonable to assume that the East European efforts concerning the functional viability of strictly socialist International Economic Organizations will also improve the chances for East-West corporations in the medium term. The further development of these organizations deserves therefore to be watched. Impulses radiating from this field may make it possible to change over to a qualitatively new kind of economic relations between East and West.
Keywords: 330; Integration